MINIMALLY INVASIVE LATERAL RETROPLEURAL APPROACH TO THE THORACOLUMBAR JUNCTION – REVIEW & EXPERIENCE - MENEZES,CRISTIANO MAGALHÃES (2020)
ABSTRACT Objective To describe the minimally invasive technique for the lateral retropleural approach to the thoracolumbar spine and its viability in several affections of the region, demonstrating its indications, potential advantages, and necessary precautions, with an emphasis on the local anatomy, especially the diaphragm. Methods After a review of the literature, the initial experience of the Service is reported, comparing it to the published results. The surgical technique used is described with emphasis on the surgical anatomy of the diaphragm. Results The minimally invasive lateral retropleural approach to the thoracolumbar junction with the application of an expandable tubular retractor was described step-by-step in this study, with emphasis on the crucial points of technical execution, such as preoperative planning, access to the retropleural plane, and an orthogonal approach for adequate discectomy and/or corpectomy and subsequent implant placement. It can be used in the treatment of deformities, degenerative diseases, trauma, tumors, and infections and it allows for adequate interbody arthrodesis fusion rates associated with a smaller skin incision and less soft tissue damage, blood loss, and postoperative pain. Thus, it results in better postoperative mobility and a shorter hospital stay, which can also be observed in the data from initial experience of this Service. Conclusions The minimally invasive technique for the lateral retropleural approach to the thoracolumbar spine with the application of an expandable tubular retractor was shown to be promising and safe for the treatment of several spinal diseases despite the complex and challenging local anatomy and it presents advantages over the morbidity rates observed in the traditional approach. Level of evidence IV; Case series.